Pembelajaran Model Pengenalan, Koneksi, Aplikasi, Refleksi dan Ekstensi dalam Perspektif Studi Islam - Isya', Muhammad Andi (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
Learning models, if managed properly will produce good academic performance of students. Students are able to answer the challenges faced today and in the future. the latest research tried to make the learning model integrated by Islamic values ??in order to minimize the scientific dichotomy in the learning process. This paper aims to describe how Learning Model Introduction, Connection, Application, Reflection and Extension in the perspective of Islamic Studies. From the discussion concluded: 1) in Islam there are two sources of divine and human learning. Divine learning resources occur directly from God such as wahy (revelation), inspiration (inspiration), and ru'ya sadiqah (true dreams), while human learning resources learn from human experience through conditioning, observation, cognition, etc. and even Models ICARE is not contradicted in Islam. 2) Introduction (???????): Every first and foremost Islamic learning is monotheism or spiritual; Connection (???): teaches the fundamental relationship between the physical and spiritual realms of the human person and the wider world begins to parse theoretical perspectives; Apply (?????): Islam is a religion of real action and not just contemplation, its mission is basically related to human affairs - social, political, economic, military and religious; Reflection (??????): Reflection of education is the progress of science in the context of Islamic education the integration of science with religion; Extend (?????): development or extension in this context has been developed with the old pesantren tradition, namely bandongan, sorongan, and watonan which indicates that memorization "is not intended as rote learning that does not make sense" but "strengthened with intelligence and understanding" .